Students' conceptions of learning in the context of an accounting degree. (4th May 2017) - Abhayawansa, Subhash; Bowden, Mark; Pillay, Soma
ABSTRACT: Students' conceptions of learning (CoL) play an important role in the learning process leading to the development of generic skills. This paper investigates whether CoL of accounting students can be developed by incorporating high-level cognitive skills progressively within the accounting curriculum. First, the study explored, using phenomenography, the variation in accounting students' CoL. The findings highlighted some nuances in accountings students' CoL and that lower-order CoL were prevalent among accounting students. However, more (less) third-year students than second-year students adopted higher- (lower-) order CoL. Upon examining the learning objectives, teaching methods and assessment of all units comprising the accounting major of the host university, evidence was found that CoL are progressively developed and shaped, albeit in a limited way, based on the levels of cognitive domain emphasised within the curriculum. The findings highlight the need for accounting educators to take a whole of the programme approach to developing higher-order CoL.